STATISTICAL DESIGN AND DEVELOPMENT OF A LIQUID ORAL FLOATING IN SITU GEL OF METFORMIN HYDROCHLORIDE FOR SUSTAINED RELEASE: PHARMACODYNAMIC AND TOXICITY (HISTOPATHOLOGY) STUDIES - MATHEWS, RASHMI; RAO, B. PRAKASH; KONDE, ABBULU; S., SUDARSHAN; TAHA, NAWRES A.; C., SURESH (International Journal of Applied Pharmaceutics, 2019)
Objective: To statistically design, optimize and evaluate a liquid oral, floating in situ gel of metformin hydrochloride (MH) to increase the gastric residence time (the absorption window being the upper part of the duodenum), sustain and modulate the release behavior of the drug. No liquid oral SR formulations of MH are yet available in the market. Methods: A simple mixing based ionic cross-linking method was used for the formulation. A Two-square Factorial Design was employed and the effect of sodium alginate and three categorical levels of HPMC (K4M, K100M, E50) on the response variables were studied. Results: The optimized formulation gelled instantaneously in simulated gastric fluid and showed>24 h floating. The drug release in 1h was 37.98 %, followed by a moderate sustained release for 12 h. Pharmacodynamic studies showed a significant reduction in blood glucose levels in Wistar rats. Short term preclinical safety studies revealed no toxicity to pancreatic tissues. On the contrary, faster regeneration of the β cells of the islets of Langerhans was observed with the group treated with the optimized formulation. Stability studies revealed a 2-year shelf life. Conclusion: An elegant, needle-free, in situ gelling, SR liquid oral of metformin hydrochloride could be developed with drug release modulated as per official specifications for SR formulations of MH. This would be an interesting alternative for geriatric patients who find it difficult to swallow bulky tablets.